Berbagi Pengetahuan dan Perilaku Kerja Inovatif: Studi Penerapan Kurikulum Merdeka Pada Guru - Indistra, Ni Nyoman Della Lies; Hernawa, Timotius Maria Raditya (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2025)
This study aims to determine the relationship between knowledge sharing and innovative work behavior among teachers implementing Kurikulum Merdeka. The participants were 134 teachers implementing Kurikulum Merdeka, coming from kindergarten/early childhood education, elementary, junior high, and senior high/vocational schools. The hypothesis is that there is a positive relationship between knowledge sharing and innovative work behavior among teachers implementing Kurikulum Merdeka. This study used a quantitative method. The scales used in this study were modified from the Knowledge Sharing Scale by Van Den Hooff and De Ridder (10 items, α = 0.947) and the Innovative Work Behavior Scale by Onne Janssen (9 items, α = 0.935). The study used Spearman's Rho test because the data was not normally distributed. The results show that the hypothesis is accepted, indicating a significant and positive relationship with a moderate strength between knowledge sharing and innovative work behavior among teachers implementing Kurikulum Merdeka (p .001, rs = 0.532). This means that the higher the level of knowledge sharing, the higher the innovative work behavior of the teachers. Conversely, the lower the level of knowledge sharing, the lower the innovative work behavior.